Bibliometric analysis of the transformative synergies between blockchain and accounting in the uprooting of economic criminality - Veronica Grosu; Daniel Botez; Anatol Melega; Rozalia Kicsi; Svetlana Mihaila; Anamaria – Geanina Macovei (Entrepreneurship and Sustainability Issues, 2022)
The impact of globalization and the growing digitalization of the economy is becoming increasingly felt in the area of economic criminality, and we therefore believe that it is a matter of urgency to seek viable and effective solutions to manage this area of concerns, thus preventing the contamination of the borderline that currently separates legal and illegal technologies, depending on how they are regulated or not. In this light, the aim of our paper is to explore those instances in which blockchain accounting has the potential to be a viable solution to guarantee the security and legality of economic and financial transactions, thereby significantly mitigating the impact and frequency of economic criminality. The main objectives we pursue are to define the nature of the interrelation among the concept of blockchain, accounting and economic criminality and to evaluate the potential advantages of implementing blockchain technology in the accounting system. The main findings are a comprehensive mapping of the network that links blockchain technology, accounting and economic criminality employing the clustering method. These are likely to be of valuable assistance not only for the legislator, but also for the shaping of future research paths in this field and, last but not least, for an essential group of stakeholders such as computer scientists, accountants, auditors and national governments.